Relationship between Anemia and Stroke Severity. A Tertiary Care Hospital Experience. - Zille-Huma; Inam E Khuda; Syeda Anjala Tahir; Samar Zaki; Shaikh Jehanzaib Saeed; Asif Ali (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: There is growing evidence that anemic patients suffer more severe strokes. We evaluated the relationship between anemia and stroke severity in our patient population. Methods: This descriptive cross-sectional study was carried out over six months in Dow University Hospital which is a tertiary care hospital in Karachi. Patients admitted with acute ischemic stroke, with symptoms duration of up to 72 hours and age more than 20 and less than 80 years were recruited. Patients were divided into two categories, anemic and non-anemic. The stroke severity was classified according to the National Institute of Health Stroke Scores (NIHSS) into three categories, i.e. mild, moderate, and severe. The demographic details, NIHSS scores at admission, symptom du- ration, and hemoglobin concentration were entered into spreadsheets and later transferred to SPSS software for statistical analyses Results: A total of 104 patients were recruited after applying inclusion and exclusion criteria, out of which 55 patients were anemic. The mean age was 54.6 (±13) years. The mean hemoglobin concentration was 10 (±2) g/dl among anemic patients while in non-anemic patients it was 13.9 (±1.2) g/dl. Anemic stroke patients were more likely to have severe strokes, compared to non-anemic patients 41 (74.5%) vs 18 (36.7%), P-value 0.001. The mean NIHSS was higher in anemic compared to non- anemic stroke patients 18.3 (±6.7) vs 13.5 (±6.6), P-value .00, (95 % CI, 2.2, 7.3). Patients with severe anemia had higher stroke severity but did not reach statistical significance (11/13,84.6% vs 48/ 91, 52.7%, P-value .02). Conclusion: Ischemic stroke patients with anemia have more severe strokes when compared to non- anemic patients. The level of hemoglobin may also be associated with stroke severity. These findings should be evaluated by more studies in stroke patients.